BASIC ACCOUNTING TRAINING: INTRODUCTION TO THE INDONESIAN RUPIAH CURRENCY AND PERSONAL FINANCIAL JOURNALS FOR CHILDREN AT PPWNI KLANG, SELANGOR, MALAYSIA - Devita Sari, Silvia; Luayyi, Sri; Srikalimah, Srikalimah (LPPM Univ. Ibn Khaldun Bogor, 2025)
Financial literacy is an essential skill that should be introduced from an early age, particularly for children in migrant communities who often face limited access to structured financial education. This community service program offered a distinctive approach by integrating the introduction of the Indonesian Rupiah as a symbol of national identity with practical financial management training for children at the Indonesian Citizens Education Center (PPWNI) in Klang, Selangor, Malaysia. The program combined short lectures, educational games, buying–selling simulations, simple journal recording, and the innovative Dream Pocket activity. A total of 73 children aged 7–12 years participated. Results indicated substantial improvements in their ability to recognize Rupiah and Ringgit, differentiate needs and wants, record daily transactions, and plan savings. Pre- and post-test results showed an increase of 40% to 70% across key aspects. Uniquely, this program not only enhanced cognitive understanding but also reinforced cultural identity and promoted character values such as discipline, responsibility, and motivation to save. These findings highlight the novelty of embedding national identity into financial literacy education, offering a replicable model for migrant communities and early childhood education contexts.